The heart specialist - Rothman, Claire, 1958- (England : Oneworld Publications, 2011)
Set in Quebec at the turn of the 19th to 20th century, the story of Agnes White, a lonely orphaned girl fascinated by the'wrong' things--microscopes, dissections, and anatomy instead of more ladylike interests--who rises to the status of one of the world's most celebrated pioneering women doctors. Not only does she break through patriarchal academic barriers; she masters the science of the human heart, becoming a scholar of international fame, all in a place and time inimical to intelligent women. Inspired by the career of Maude Abbott, one of Canada's first female physicians.
Originally published: Canada : Cormorant Books, 2009.
Keywords: Women physicians -- fiction; Self-realization in women -- Fiction; Montreal (Quebec) -- Fiction